Inglés técnico, Módulo: Avanzado - Tena Colunga, José (My University, 1995)
Technical language is distinguished from natural language by the frequency of occurrence of terms to which meanings have been assigned whiting specific intellectual disciplines or fields of technology. Technical texts are also characterized by the consistent us of certain conventions of presentation. The terms of technical discourse refer to bodies of knowledge outside the general experience of the great majority of the speakers of a language; hence texts with a high density of such terms are often not immediately comprehensible to non-specialist readers.
Keywords: composición; traducción; computer; gramaticales; paradox